PENGARUH PENDAPATAN ASLI DAERAH DAN DANA ALOKASI KHUSUS TERHADAP BELANJA MODAL (Studi Pada Kabupaten/Kota Di Sulawesi Tengah) - Elni Elni (Katalogis, 2016)
The objectiveof this research is to determine and analyze the development of local revenues, specific allocation funds, and capital expenditures and the effect of of local revenues and specific allocation funds on capital expenditures both simultaneously and partially. The sample in this research consists of 11 regencies/cities in Central Sulawesi and sample tehnique is purposive sampling. Method of data analysis is trend analysis and multiple linear regressions. The results shows that in average, the growth of local revenues tends to increase within 3 budget years, while the average growth of specific allocation funds tends to decrease. The average growth of capital expenditure tends to decrease in accordance to the average growth of specific allocation funds. Simultaneous test indicates that local revenues and specific allocation funds affect the capital expenditure positively and significantly. Partial test shows that local revenues and specific allocation funds affect capital expenditure positively and significantly. Determinant coefficient demostrates the R-square value of 0,667 that shows that 66,70% of capital expenditure affected by local revenues and specific allocation funds; the remaining of 33,30% affected by other variables that are not studied.